1972
DOI: 10.1071/bi9721133
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis of Tropical Pasture Plantsiv. Basis and Consequences of Differences Between Grasses and Legumes

Abstract: Ab8tractDifferences in leaf net photosynthetic rate were associated with differences in intracellular resistance. The larger intracellular resistance of legume leaves appeared to result from larger resistances to the movement of C02 from the mesophyll cell wall to the photosynthetic sites rather than from high resistances associated with its fixation at the sites.Photorespiration could not be detected in grasses but their dark respiration rates at normal ambient C02 concentrations were higher than the values f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

1975
1975
1996
1996

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 24 publications
3
17
0
1
Order By: Relevance
“…Although the physical component of mesophyll resistance dependent upon cell size is influenced by growth temperature (Wilson 1970), it seems more likely that the higher rM of plants grmvn at 20°0 resulted from a higher value of the chemical component because rM decreased during 15 hr of acclimatization. The fact that growth temperature had little effect on the initial slope of the light response curve (Fig.…”
Section: Results and Disoussion (A) Temperature Historymentioning
confidence: 99%
See 2 more Smart Citations
“…Although the physical component of mesophyll resistance dependent upon cell size is influenced by growth temperature (Wilson 1970), it seems more likely that the higher rM of plants grmvn at 20°0 resulted from a higher value of the chemical component because rM decreased during 15 hr of acclimatization. The fact that growth temperature had little effect on the initial slope of the light response curve (Fig.…”
Section: Results and Disoussion (A) Temperature Historymentioning
confidence: 99%
“…1) and hence the photochemical component of rM (excitation resistance, Monteith 1963) but has a marked effect on photosynthetic enzyme activity (Treharne and Eagles 1970) suggests that the biochemical component is involved. This could have arisen from a deficiency of photosynthetic enzymes or from an accumulation of photosynthate associated with the slow growth at 20°0 (Woledge and Jewiss 1969;Ludlow and Wilson 1970), and the decrease in rM during acclimatization could have resulted from respiration of the accumulated photosynthate or an increase in enzyme activity. There are data showing rapid changes in enzyme activity in response to illuminance (Hatch, Slack, and Bull 1969) but none for temperature.…”
Section: Results and Disoussion (A) Temperature Historymentioning
confidence: 99%
See 1 more Smart Citation
“…These higher rates result mainly from lower intracellular resistances associated with the C4 pathway of photosynthesis and the apparent absence of photorespiration [11 ]. A comparison of these two species in pure stands of each showed that the grass has more erect leaves [4], while the stomatal resistance of C4 grasses in the field is higher than that of legumes (unpublished data).…”
Section: Comparative Photosynthetic Rates Of Grass and Legume Leavesmentioning
confidence: 99%
“…In this model 'mesophyll' resistance is sometimes called to 'transport' resistance (JONES and SLATYER, 1972) or 'liquid phase' resistance (FARQUHAR and SHARKEY, 1982) to be distinguished from `carboxylation' resistance . From 1970s there have been several studies trying to separate 1/gm and 1/gx by, e.g., CHARTIER et al (1970) , JONES and SLATYER (1972) , LUDROW andWILSON (1972) , andPRIOUL (1976) . In these studies mesophyll resistance was calculated to be very large compared with carboxylation resistance.…”
Section: Appendixmentioning
confidence: 99%